The analysis of interjections types and emotional state used in “Sam & Cat” sitcom (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
Interjections in an everyday speech frequently serve as pragmatic markers, initiating utterances and connecting them to the preceding interaction. Interjections can happen in three different types: primary emotive interjections, primary cognitive interjections, and secondary volitive interference. Thus, the present study aims at analyzing the interjection types and emotional state in the “Sam & Cat” sitcom. This research focused more on 5 episodes in this sitcom. This qualitative research is conducted by observing and analyzing the conversation between two main characters in the sitcom. Using the theory that discuss those three types of interjections and twenty one emotion states, the researchers discovered some results. According to the data, the most common use is primary emotive interjections that appeared 50 times. Continued with primary cognitive interjections that appeared 33 times and secondary volitive interjections that use 26 times. Furthermore, there are three emotional states with the same amount: imitation, contempt, and enthusiasm. These emotional states express the main character's situation that appears 14 times. However, triumph and wonder are two emotional states that have not appeared in those 5 episodes.